1979
DOI: 10.1002/clc.4960020603
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plasma concentrations of thromboxane B2 in prinzmetal's variant angina and classical angina pectoris

Abstract: We have reported that thromboxane B2 is present in plasma of Prinzmetal's angina patients measured by radioimmunoassay but is below detection limits, <0.5 pmol/ml, in normals. To determine whether this metabolite of thromboxane A2 (a coronary vasoconstrictor) is present in the peripheral blood in classical angina pectoris, we studied 14 patients with fixed obstructive coronary artery disease (2.5 lesions per patient) in whom angina was induced by atrial pacing. Thromboxane B2 at rest was barely detectable (0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1980
1980
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…Elevated levels of thromboxane B, have been found in the peripheral blood in Prinzmetal's variant angina (60) and in coronary sinus blood in patients with vasotonic angina (61). Robertson et al (62) reported a five-fold increase in the concentration of coronary sinus thromboxane B, in spontaneous ischaemia.…”
Section: Coronary Arterial Spasmmentioning
confidence: 99%
“…Elevated levels of thromboxane B, have been found in the peripheral blood in Prinzmetal's variant angina (60) and in coronary sinus blood in patients with vasotonic angina (61). Robertson et al (62) reported a five-fold increase in the concentration of coronary sinus thromboxane B, in spontaneous ischaemia.…”
Section: Coronary Arterial Spasmmentioning
confidence: 99%
“…Myocardial ischemia associated with coronary vasospasm as seen in Prinzmetal's angina is associ ated with increased levels of TxB 2 when measured during or within 5 to 10 minutes postangina. 44 Stable angina pectoris is associated with little or no elevation of platelet markers in the blood, but if a myocardial infarction in the past has resulted in left ventricular dysfunction there is an elevation of BTG. 22,59 Acute myocardial infarction results in an eleva tion of both PF4 and BTG but the PF4 levels are near normal and return to normal soon, whereas levels of BTG may remain elevated for a month or more.…”
Section: Coronary Artery Disordersmentioning
confidence: 99%
“…Although measurement of the clot formation or dissolution has provided a means to screen hemostasis and monitor anticoagulant therapy for over a quarter of a century, it suffers from many drawbacks. 8,9,11,19,26,[35][36][37][38]43,59,61,68,69,73,78,81,85,86,93,116 Most assays only identify bleeding problems and do not necessarily provide an overall hemostatic picture for a given patient, since the individual para metric alterations vary widely (for example, activa tion of factors or consumption of inhibitors). Table 5 depicts various methods that can be used to quantitate the molecular markers of hemostatic activation.…”
Section: Molecular Markers Of Hemostatic Disordersmentioning
confidence: 99%